Electrolytic capacitor separators and electrolytic capacitors
Patent Information
- Application Number
- JP2025058837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0013】 本発明により、耐電解液性、吸水性に優れ、凹付きの発生が抑制された電解コンデンサ用セパレータと、ESRが低い電解コンデンサを提供することができる。
Smart Images

Figure 2026166097000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a separator for electrolytic capacitors and an electrolytic capacitor. Hereinafter, the "separator for electrolytic capacitors" may be abbreviated as "separator". In addition, the "electrolytic capacitor" may be abbreviated as "capacitor".
Background Art
[0002] Electrolytic capacitors (electrolytic capacitors) using an electrolytic solution are widely used in various electronic devices, and their applications cover a wide range including charge accumulation, noise removal, and phase adjustment.
[0003] Conventionally, as separators for electrolytic capacitors, paper separators in which a paper strength enhancer is adhered to paper mainly composed of hemp pulp or esparto pulp (see, for example, Patent Documents 1 to 3), and paper separators made of beaten raw material of regenerated cellulose fiber and natural pulp (see, for example, Patent Document 4) have been used.
[0004] Patent Document 5 discloses a separator comprising beaten solvent-spun cellulose fibers, viscose rayon, and polyvinyl alcohol binder fibers. Patent Document 6 discloses a separator for electrochemical elements, which comprises beaten solvent-spun cellulose fibers and rayon fibers.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Patent Document 2
Patent Document 3
Patent Document 4
Patent Document 5
[0006] When the separators described in Patent Documents 1 to 4 were used at higher temperatures than conventional ones, such as when incorporated into equipment located near the drivetrain of an automobile, the fibers would deteriorate due to the action of the electrolyte solvent, resulting in a deterioration of their lifespan characteristics.
[0007] The separator disclosed in Patent Document 5 sometimes exhibited indentations on its surface when placed in a high-humidity environment due to the high hygroscopicity of the polyvinyl alcohol binder fibers.
[0008] The separator disclosed in Patent Document 6 is required to have further solvent resistance and heat resistance to cope with the changes in electrolytes and environmental conditions used in electrolytic capacitors in recent years. While these requirements can be improved by using a moist heat adhesive binder such as polyvinyl alcohol binder fiber, a problem arises when a moist heat adhesive binder is used, resulting in the appearance of indentations on the separator surface.
[0009] In this specification, "recession on the separator surface" refers to the occurrence of irregularities on the surface of the separator, and the degree of defect in recession is determined based on the depth (height) of the recessed portion. Figures 1 to 3, described later, show the criteria for the degree of recession.
[0010] The object of the present invention is to provide an electrolytic capacitor separator with excellent electrolyte resistance and water absorption properties, and in which the occurrence of indentations is suppressed, as well as an electrolytic capacitor with low ESR. [Means for solving the problem]
[0011] The above problem was solved by the following means.
[0012] (1) A separator for electrolytic capacitors made of a wet-laid nonwoven fabric, wherein the wet-laid nonwoven fabric contains 30 to 60 mass% of beaten solvent-spun cellulose fibers, 30 to 60 mass% of rayon fibers, and 3 to 20 mass% of wet heat-adhesive binder fibers, and has an average pore size of 0.4 to 3.0 μm and a maximum pore size of 3.0 to 13.0 μm. (2) The separator for electrolytic capacitors according to (1), wherein the wet heat-adhesive binder fibers are polyvinyl alcohol fibers. (3) The separator for electrolytic capacitors according to (1) or (2), wherein the beaten solvent-spun cellulose fibers have a modified freeness of 75 ml or more and 220 ml or less. Modified freeness: a value measured in accordance with JIS P8121-2:2012, except that an 80-mesh wire mesh with a wire diameter of 0.14 mm and an opening of 0.18 mm is used as the sieve plate, and the sample concentration is set to 0.1 mass%. (4) An electrolytic capacitor comprising the separator for electrolytic capacitors according to any one of (1) to (3).
Effects of the Invention
[0013] According to the present invention, it is possible to provide a separator for electrolytic capacitors that is excellent in electrolytic solution resistance and water absorbency and in which the occurrence of dents is suppressed, and an electrolytic capacitor with low ESR.
Brief Description of the Drawings
[0014] [Figure 1] Figure 1 is a photograph showing an example of a separator with a dent evaluation of ○. [Figure 2] Figure 2 is a photograph showing an example of a separator with a dent evaluation of Δ. [Figure 3] Figure 3 is a photograph showing an example of a separator with a dent evaluation of ×.
Modes for Carrying Out the Invention
[0015] <Electrolytic Capacitor> An electrolytic capacitor is a capacitor having a power storage function, which is configured with a dielectric interposed between two opposing electrodes, and has functions such as noise absorption and resonance in addition to the power storage function. Examples of the electrolytic solution include liquids obtained by dissolving ion-dissociable salts in organic solvents such as γ-butyrolactone (GBL), dimethylformamide (DMF), tetrahydrofuran (THF), dimethoxyethane (DME), dimethoxymethane (DMM), sulfolane (SL), dimethyl sulfoxide (DMSO), ethylene glycol, and propylene glycol. Examples of the electrolytic capacitor include aluminum electrolytic capacitors that use aluminum foil as electrodes.
[0016] <Separator for Electrolytic Capacitors> As the raw material for the separator for electrolytic capacitors of the present invention, beaten solvent-spun cellulose fibers are used. The solvent-spun cellulose fibers mean cellulose fibers obtained by directly dissolving cellulose in an organic solvent without going through a cellulose derivative. The solvent-spun cellulose fibers are sometimes referred to as "Lyocell (registered trademark)" or "Tencel (registered trademark)". Effects brought by the beaten solvent-spun cellulose fibers include that the fibers form a fine structure inside the separator, thereby improving the electrolyte retention property, and that the pores are reduced to make internal short circuits less likely to occur.
[0017] In the present invention, the beaten solvent-spun cellulose fibers have molecules highly aligned in the longitudinal direction of the fiber axis, so that when a mechanical force such as friction is applied in a wet state, the fibers are easily refined to generate thin and long fine fibers. Compared with beaten natural cellulose fibers and bacterial cellulose fibers, the beaten solvent-spun cellulose fibers are less likely to form a film and firmly hold the electrolytic solution between the fine fibers, thus exhibiting excellent electrolytic solution absorbency and retention properties.
[0018] In the present invention, methods for producing solvent-spun cellulose fibers by beating include dispersing short fibers of solvent-spun cellulose in water or the like at an appropriate concentration, and beating them using a refiner, beater, mill, grinding device, rotary blade homogenizer that applies shearing force with high-speed rotating blades, double-cylinder high-speed homogenizer that generates shearing force between a high-speed rotating cylindrical inner blade and a fixed outer blade, ultrasonic crusher that pulverizes by ultrasonic impact, and high-pressure homogenizer that applies shearing or cutting force to the fibers by applying a pressure difference of at least 20 MPa to the fiber suspension, passing it through a small-diameter orifice to increase its speed, and then rapidly decelerating it by impact. In particular, the method of beating using a refiner is preferred.
[0019] The modified filtration volume of the beaten solvent-spun cellulose fibers is preferably 75 ml to 220 ml, more preferably 90 ml to 175 ml, and even more preferably 90 ml to 120 ml. If the modified filtration volume is greater than 220 ml, the density of the separator may become insufficient, leading to a high rate of short-circuit failures or low electrolyte absorption and retention. If the modified filtration volume is less than 75 ml, the density of the separator may become too high, resulting in a high ESR.
[0020] Modified filtration efficiency refers to the value measured in accordance with JIS P8121-2:2012, except that an 80-mesh wire mesh with a wire diameter of 0.14 mm and a mesh opening of 0.18 mm was used as the sieve plate, and the sample concentration was set to 0.1 mass%.
[0021] The length-weighted average fiber length of the beaten solvent-spun cellulose fibers is preferably 0.2 mm to 3.0 mm, more preferably 0.2 mm to 2.0 mm, and even more preferably 0.2 mm to 1.6 mm. If the length-weighted average fiber length is shorter than 0.2 mm, a larger proportion may fall through the papermaking screen during wet papermaking and be washed away into the wastewater, or fuzzing may occur on the separator surface due to friction. If the length-weighted average fiber length is longer than 3.0 mm, the fibers may tangle and form clumps, resulting in uneven thickness.
[0022] The length-weighted average fiber length of solvent-spun cellulose fibers obtained by beating can be measured using the Kajaani FiberLab V3.5 (Metso Automation). The Kajaani FiberLab V3.5 (Metso Automation) can measure the total true length (L) of the bent fiber and the shortest lengths (l) of both ends of the bent fiber for each individual fiber passing through the detection unit. The "length-weighted average fiber length" is the length-weighted average fiber length calculated from the projected fiber length, which is the shortest length (l) of both ends of the bent fiber.
[0023] The content of the beaten solvent-spun cellulose fibers is 30 to 60% by mass, more preferably 35 to 58% by mass, and even more preferably 40 to 55% by mass, relative to the total amount of fibers in the separator. If the content is less than 30% by mass, the water absorption will be low. If the content exceeds 60% by mass, the separator will become too dense, and the ESR will be high.
[0024] The separator for electrolytic capacitors of the present invention uses rayon fibers. Preferably, the rayon fibers used in the present invention are unbeaten fibers. Both rayon fibers and solvent-spun cellulose fibers are cellulosic fibers. The advantages of using rayon fibers include an increased contact area between the rayon fibers and the beaten solvent-spun cellulose fibers due to the surface irregularities and flattened shape of the rayon fibers, and an increased strength of the separator due to hydrogen bonding between the cellulosic fibers.
[0025] The average fiber diameter of the rayon fibers used in this invention is preferably 5.0 μm or more and 9.5 μm or less, more preferably 5.5 μm or more and 9.3 μm or less, and even more preferably 6.0 μm or more and 9.0 μm or less. If the average fiber diameter of the rayon fibers exceeds 9.5 μm, the number of fibers in the thickness direction decreases, which may result in weaker separator strength or poorer liquid absorption. If the average fiber diameter of the rayon fibers is less than 5.0 μm, the separator may become too dense, resulting in a high ESR. The average fiber diameter of the rayon fibers is the average value of the fiber diameters of the fibers when they are contained in the separator. The average fiber diameter can be determined as follows.
[0026] 1) Observe the cross-section of the separator under a microscope and take a photograph of the fiber cross-section. 2) To eliminate diagonally cut fibers, select 20 fibers in which the ratio of the longitudinal fiber diameter to the transverse fiber diameter in the cross-section of the fiber is 1:2 to 2:1. 3) Measure the cross-sectional area of the selected fiber. 4) Assuming the cross-sectional shape is a perfect circle, calculate the fiber diameter from the cross-sectional area. The average of the fiber diameters of 20 fibers is taken as the fiber diameter.
[0027] The separator of the present invention includes rayon fibers, as well as beaten solvent-spun cellulose fibers and moist heat-adhesive binder fibers. Those skilled in the art can distinguish these fibers in a microscopic photograph and measure the fiber diameter of each fiber. The beaten solvent-spun cellulose fibers are fine fibers. The rayon fibers are thicker than the beaten solvent-spun cellulose fibers and have grooves. The moist heat-adhesive binder fibers are fused together and have an expanded shape.
[0028] In the present invention, the rayon fiber content is 30 to 60% by mass of the total fibers contained in the separator, more preferably 32 to 55% by mass, and even more preferably 35 to 50% by mass. If the content is less than 30% by mass, the separator becomes too dense and the ESR increases. If the content exceeds 60% by mass, the water absorption deteriorates.
[0029] The separator for electrolytic capacitors of the present invention uses moist heat adhesive binder fibers. Moist heat adhesive binder fibers are fibers that, in a wet state, flow from a fibrous state at a certain temperature, or easily deform to exhibit adhesive function. Specifically, these are thermoplastic fibers that can be softened with hot water or steam (for example, around 80-120°C) to self-adhere or adhere to other fibers. Examples include polyvinyl fibers (polyvinylpyrrolidone, polyvinyl ether, polyvinyl alcohol, polyvinyl acetal, etc.), cellulose fibers (C1-3 alkylcellulose such as methylcellulose (C indicates the number of carbon atoms), hydroxyC1-3 alkylcellulose such as hydroxymethylcellulose, carboxyC1-3 alkylcellulose such as carboxymethylcellulose, or salts thereof), and fibers made of modified vinyl copolymers (polymers of vinyl monomers such as isobutylene, styrene, ethylene, vinyl ether, etc., and unsaturated carboxylic acids such as maleic anhydride, or their anhydrides, or salts thereof). As the moist heat adhesive binder fiber used in the present invention, polyvinyl fiber is preferred, and polyvinyl alcohol (PVA) fiber (vinylon fiber) is more preferred, because it increases the strength of the separator.
[0030] The average fiber diameter of the moist heat-adhesive binder fibers is preferably 3.0 μm to 15.0 μm, more preferably 6.0 μm to 13.0 μm, and even more preferably 7.0 μm to 11.0 μm. By setting the fiber diameter within this range, a separator with excellent strength in a wet state and a uniform form can be obtained. The average fiber length of the moist heat-adhesive binder fibers is preferably 1 to 15 mm, more preferably 2 to 10 mm, and even more preferably 3 to 5 mm. By setting the fiber length within this range, the moist heat-adhesive binder fibers will not fall off the papermaking wire during papermaking, and a separator with sufficient strength can be obtained.
[0031] The content of the moist heat-adhering binder fibers is 3 to 20% by mass, more preferably 4 to 15% by mass, and even more preferably 5 to 10% by mass, relative to the total amount of fibers in the separator. If the content is less than 3% by mass, the electrolyte resistance decreases. If the content exceeds 20% by mass, the micropores of the separator become clogged, and the ESR increases.
[0032] The electrolytic capacitor separator of the present invention contains 30-60% by mass of beaten solvent-spun cellulose fibers, 30-60% by mass of rayon fibers, and 3-20% by mass of moist heat-adhesive binder fibers, thereby suppressing the formation of indentations when the separator is placed in a high-humidity environment.
[0033] The electrolytic capacitor separator of the present invention may contain, as necessary, various fibers in a range that does not impair performance, in addition to beaten solvent-spun cellulose fibers, rayon fibers, and moist heat-adhesive binder fibers. For example, single fibers or composite fibers made from resins such as solvent-spun cellulose or regenerated cellulose short fibers, natural cellulose fibers, pulped or fibrilized natural cellulose fibers, polyolefins, acrylics, fully aromatic polyesters, fully aromatic polyesteramides, polyamides, semi-aromatic polyamides, fully aromatic polyamides, fully aromatic polyethers, fully aromatic polycarbonates, fully aromatic polyazomedines, polyimides, polyamide-imide (PAI), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), poly-p-phenylenebenzobisoxazole (PBO), polybenzimidazole (PBI), polytetrafluoroethylene (PTFE), and ethylene-vinyl alcohol copolymers may be contained in appropriate amounts individually or in combination of two or more types. Furthermore, various types of split composite fibers may be included. Semi-aromatic refers to materials that have, for example, fatty acid chains as part of their main chain. The fully aromatic polyamide may be either para-type or meta-type.
[0034] In the present invention, the content of fibers other than beaten solvent-spun cellulose fibers, rayon fibers, and moist heat-adhesive binder fibers is preferably less than 10% by mass. If the content of these fibers is 10% by mass or more, the separator strength may deteriorate or the ESR may increase.
[0035] The average pore size of the electrolytic capacitor separator of the present invention is 0.4 to 3.0 μm, more preferably 0.4 to 2.0 μm, and even more preferably 0.4 to 1.0 μm. If the average pore size is less than 0.4 μm, the separator becomes too dense, resulting in a high ESR. If the average pore size exceeds 3.0 μm, the separator lacks sufficient density, leading to decreased water absorption.
[0036] In this invention, the average pore size can be the average pore size of the separator determined from the pore size distribution measured using a palm porometer CFP-1500A manufactured by PMI Corporation, in accordance with the half-dry test method (ASTME1294-89).
[0037] The maximum pore diameter of the electrolytic capacitor separator of the present invention is 3.0 to 13.0 μm, more preferably 3.1 to 10.0 μm, and even more preferably 3.2 to 8.0 μm. If the maximum pore diameter is less than 3.0 μm, the separator becomes too dense, resulting in a high ESR. If the maximum pore diameter exceeds 13.0 μm, the separator lacks sufficient density, leading to decreased water absorption.
[0038] In this invention, the maximum pore diameter can be the maximum pore diameter of the separator measured using a PMI palm porometer CFP-1500A, in accordance with the bubble point method (ASTM F316-86).
[0039] In the present invention, methods for producing a separator with an average pore diameter of 0.4 to 3.0 μm and a maximum pore diameter of 3.0 to 13.0 μm include adjusting the fiber diameter, fiber content, basis weight of the separator, and thickness of the separator, as well as selecting a papermaking mesh in the wet papermaking method.
[0040] The basis weight of the electrolytic capacitor separator of the present invention is 8 to 22 g / m². 2 Preferably, 9-20 g / m 2 More preferably, 10-18 g / m 2 A basis weight of 22 g / m² is even more preferable. 2 If it exceeds this, the ESR may become too high. (Basis weight 8g / m²) 2 If the basis weight is less than the specified value, it may be difficult to obtain sufficient strength or the water absorption may decrease. The basis weight is measured according to the method specified in JIS P 8124:2011 (Paper and cardboard - Method for determining basis weight).
[0041] The thickness of the electrolytic capacitor separator of the present invention is preferably 15 to 60 μm, more preferably 20 to 55 μm, and even more preferably 25 to 50 μm. If the thickness exceeds 60 μm, the ESR may become too high. If the thickness is less than 15 μm, the water absorption may decrease. The thickness is determined by measuring 10 separators stacked together using an outside micrometer under a 5 N load, based on the method specified in JIS C2300-2:2010, and dividing the result by 10.
[0042] The separator for electrolytic capacitors of the present invention is a wet-type nonwoven fabric manufactured by a wet papermaking method. The wet papermaking method is a method of producing a wet-type nonwoven fabric by dispersing fibers in water to form a uniform papermaking slurry and then using a papermaking machine to produce this slurry. Examples of papermaking machines include those that use papermaking meshes such as cylindrical mesh, elongated mesh, inclined mesh, and inclined short mesh individually, as well as composite papermaking machines that combine multiple such papermaking meshes. In the process of manufacturing the wet-type nonwoven fabric, water entanglement treatment may be performed as needed. The wet-type nonwoven fabric may also be subjected to processing treatments such as heat treatment, calendering, and thermal calendering.
[0043] The electrolytic capacitor separator of the present invention has predetermined ranges for the type of fibers contained in the separator, the proportion of each fiber, the average pore diameter of the separator, and the maximum pore diameter of the separator. As a result, it is possible to produce an electrolytic capacitor separator with excellent electrolyte resistance and water absorption, suppressed occurrence of indentations, and an electrolytic capacitor with low ESR. In particular, even when using moist heat adhesive binder fibers, it is possible to produce an electrolytic capacitor separator that suppresses the occurrence of indentations. Furthermore, by using the electrolytic capacitor separator of the present invention, it is possible to create an electrolytic capacitor with a low ESR. [Examples]
[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0045] [Table 1]
[0046] <Solvent-spun cellulose fibers obtained by beating> A1: Solvent-spun cellulose fibers obtained by beating a modified filtration of 75 ml of water. A2: Solvent-spun cellulose fibers that have been beaten and filtered to a modified degree of 90 ml. A3: Solvent-spun cellulose fibers obtained by beating with a modified filtration rate of 220 ml. A4: Solvent-spun cellulose fibers obtained by beating with a modified filtration rate of 230 ml. <Rayon fiber> B1: Rayon fiber with a fiber diameter of 5.0 μm and a fiber length of 3 mm. B2: Rayon fiber with a fiber diameter of 8.1 μm and a fiber length of 3 mm. B3: Rayon fiber with a fiber diameter of 9.5 μm and a fiber length of 5 mm. <Moist heat adhesive binder fibers> C1: Polyvinyl alcohol moist heat adhesive fiber with a fiber diameter of 7.0 μm and a fiber length of 3 mm (VPB041-3, manufactured by Kuraray Co., Ltd.) C2: Polyvinyl alcohol moist heat adhesive fiber with a fiber diameter of 10.3 μm and a fiber length of 5 mm (VPB102 manufactured by Kuraray Co., Ltd.) C3: Ethylene-vinyl alcohol fiber with a fiber diameter of 8.2 μm and a fiber length of 5 mm (S030, manufactured by Kuraray Co., Ltd.) <Other Fibers> D1: Fully aromatic polyamide fiber with a fiber diameter of 12.2 μm and a fiber length of 6 mm. D2: Fibrillated total aromatic polyamide with modified filtration rate of 350 ml D3: Modified filtration method, 500ml hemp pulp
[0047] <Separator> (Examples 1-9) Papermaking slurry prepared according to the raw materials and proportions shown in Table 1 was wet-processed using a cylinder-mesh / inclined combination papermaking machine, and then calendered to adjust the thickness to produce the separators shown in Examples 1 to 9 in Table 2.
[0048] (Comparative Examples 1-10) Papermaking slurry prepared according to the raw materials and proportions shown in Table 1 was wet-processed using a cylinder-mesh / inclined combination papermaking machine, and then calendered to adjust the thickness to produce the separators shown in Comparative Examples 1 to 10 in Table 2.
[0049] [Table 2]
[0050] <Fabrication of evaluation electrolytic capacitors for Examples 1-9 and Comparative Examples 1-10> A wound element was fabricated by using chemically etched aluminum foil as the anode and unetched aluminum foil as the cathode, with the separators of Examples 1-9 and Comparative Examples 1-10 sandwiched between them. An electrolyte solution with γ-butyrolactone as the main solvent and triethylamine phthalate as the main solute was injected into the wound element, and the element was sealed to fabricate an electrolytic capacitor with a rated voltage of 25V.
[0051] <Electrolyte resistance evaluation> Five test specimens measuring 50 mm wide x 250 mm long were taken and immersed in γ-butyrolactone, which is used as a non-aqueous solvent for the electrolyte, and stored for 7 days in an atmosphere of 150 ± 1°C. After that, the test specimens removed from the γ-butyrolactone were washed with ethanol and dried to be used as separators after electrolyte immersion. Using a benchtop material testing machine (manufactured by Orientec Co., Ltd., product name STA-1150), the tensile strength in the MD direction of the separators before and after electrolyte immersion was measured in accordance with JIS P8113:2006, with a test specimen width of 50 mm, a gripping distance of 100 mm, and an elongation speed of 200 mm / min. The tensile strength before electrolyte immersion was denoted as T, and the tensile strength after electrolyte immersion as T2. The strength retention rate after electrolyte immersion was calculated using the following formula and evaluated using the following index. A high strength retention rate after electrolyte immersion indicates good electrolyte resistance.
[0052] Strength retention rate after immersion in electrolyte solution (%) = T2 / T × 100 index ○: 80% or higher. △: 75% or more, but less than 80%. ×: Less than 75%.
[0053] <Water absorption evaluation> A separator test piece measuring 20 mm wide x 200 mm long was conditioned for 24 hours in a constant temperature and humidity chamber at 23°C and 50% relative humidity. Then, only the bottom 10 mm of the test piece in the vertical direction was immersed in deionized water and fixed in place. The water absorption capacity (mm) was measured by the height of the deionized water absorbed in 10 minutes and evaluated using the following indicators.
[0054] index ○: 30mm or more. △: 25mm or more, less than 30mm. ×: Less than 25mm.
[0055] <Dimpled rating> A separator test specimen measuring 200 mm in width x 200 mm in length was conditioned for 4 hours in a constant temperature and humidity chamber at 23°C and 90% relative humidity. The surface of the specimen was then visually observed for indentation and evaluated using the following indicators. A specimen without indentation is considered good.
[0056] Criteria ○: No dents are present. △: Shallow dents are observed. ×: Large (deep) dents are observed. The criteria for dents are shown in Figures 1 to 3. Figure 1 is a photograph showing an example of a separator with a dent evaluation of ○, Figure 2 is a photograph showing an example of a separator with a dent evaluation of △, and Figure 3 is a photograph showing an example of a separator with a dent evaluation of ×.
[0057] <ESR Evaluation> The ESR of the electrolytic capacitors of Examples and Comparative Examples was measured using an LCR meter at 20°C and a frequency of 1 kHz, and evaluated according to the following criteria.
[0058] Criteria ○: Less than 70 mΩ. △: 70 mΩ or more and less than 75 mΩ. ×: 75 mΩ or more.
[0059]
Table 3
[0060] The separators for electrolytic capacitors of Examples 1 to 9 are wet-laid nonwoven fabrics containing 30 to 60 mass% of beaten solvent-spun cellulose fibers, 30 to 60 mass% of rayon fibers, and 3 to 20 mass% of wet-heat adhesive binder fibers, with an average pore size of 0.4 to 3.0 μm and a maximum pore size of 3.0 to 13.0 μm. Thus, none of the items including electrolytic solution resistance, water absorbency, dents, and ESR received an × evaluation, and the evaluation results were excellent. In particular, the separators for electrolytic capacitors of Examples 4 and 17 received an ○ evaluation for all items of electrolytic solution resistance, water absorbency, dents, and ESR, and showed particularly excellent evaluation results.
[0061] On the other hand, the separator for electrolytic capacitors of Comparative Example 1 had a low content of beaten solvent-spun cellulose fibers, so dents were observed on the separator.
[0062] The separator for the electrolytic capacitor in Comparative Example 2 had a high content of solvent-spun cellulose fibers that had been beaten, resulting in indentations in the separator. Furthermore, the capacitor's ESR was inferior.
[0063] The separator for the electrolytic capacitor in Comparative Example 3 showed indentations due to its low rayon fiber content.
[0064] The electrolytic capacitor separator in Comparative Example 4 had a high rayon fiber content, resulting in poor water absorption and the observation of indentations in the separator.
[0065] The electrolytic capacitor separator in Comparative Example 5 had poor electrolyte resistance because it contained a small amount of moist heat adhesive binder fibers.
[0066] The separator for the electrolytic capacitor in Comparative Example 6 exhibited indentation due to its high content of moist heat-adhesive binder fibers. Furthermore, the capacitor's ESR was inferior.
[0067] The electrolytic capacitor separator in Comparative Example 7 had a small average pore diameter and a small maximum pore diameter, resulting in a poor ESR of the capacitor.
[0068] The electrolytic capacitor separator in Comparative Example 8 had poor water absorption due to its large average and maximum pore diameters.
[0069] The electrolytic capacitor separator in Comparative Example 9 did not contain beaten solvent-spun cellulose fibers or rayon fibers, and therefore had poor water absorption and capacitor ESR.
[0070] Comparative Example 10, an electrolytic capacitor separator, lacked moist heat-adhesive binder fibers, resulting in poor electrolyte resistance. Furthermore, its large average and maximum pore sizes led to poor water absorption. [Industrial applicability]
[0071] The electrolytic capacitor separator of the present invention can be suitably used in electrolytic capacitors.
Claims
1. A separator for electrolytic capacitors made of a wet nonwoven fabric, characterized in that the wet nonwoven fabric contains 30 to 60% by mass of solvent-spun cellulose fibers obtained by beating, 30 to 60% by mass of rayon fibers, and 3 to 20% by mass of moist heat-adhesive binder fibers, and has an average pore size of 0.4 to 3.0 μm and a maximum pore size of 3.0 to 13.0 μm.
2. The separator for electrolytic capacitors according to claim 1, wherein the moist heat adhesive binder fiber is a polyvinyl alcohol fiber.
3. The electrolytic capacitor separator according to claim 1, wherein the modified filtration rate of the beaten solvent-spun cellulose fibers is 75 ml or more and 220 ml or less. Modified filtration efficiency: The value was measured in accordance with JIS P8121-2:2012, except that an 80-mesh wire mesh with a wire diameter of 0.14 mm and a mesh opening of 0.18 mm was used as the sieve plate, and the sample concentration was set to 0.1 mass%.
4. An electrolytic capacitor containing the separator for electrolytic capacitors described in any one of claims 1 to 3.
Citation Information
Patent Citations
Electrolytic capacitor
JP2001267182A
Electrolytic capacitor
JP2004200395A
Electrolytic capacitor
JP2004228600A
Alkali battery separator and alkali battery
JP2017157349A
Separator for electrochemical element and electrochemical element arranged by use thereof
JP2018139283A